Réceptions croisées du Cancioneiro alegre de poetas portuguezes e brazileiros (1879) de Camilo Castelo Branco : la formation d’un espace littéraire luso-brésilien sous tension - Sébastien Rozeaux (Amnis)
This study is based on the cross-analysis of the reception, in Portugal and in Brazil, of a jocose and humorous poetry anthology in which Portuguese man of letters Camilo Castelo Branco included a few compositions by Brazilian poets. Despite the high expectations surrounding the publication of the work in Brazil, the Cancioneiro alegre de poetas portuguezes e brazileiros, published in 1879, was the target of very harsh criticisms, so much so that, a few months later, a pamphlet came out, in which the Portuguese writer himself replied to his detractors, whether Portuguese or Brazilian. The transnational analysis of the stakes of that controversy should be instrumental in understanding the obvious discrepancies characterizing the reception of the book. Beyond that, that controversy, which only lasted for a few months, sheds light on the forming process of a Luso-Brazilian space of literary exchanges in the second half of the nineteenth century (favoring literary circulations between the two Portuguese-speaking nations). The unheard-of intensity of these exchanges at a time when the Brazilian Letras Patrias were being elaborated created tensions epitomized by the archetypal episode exposed in this study.